Experiences, obstacles and challenges in the study of impact and effectiveness of KTP (community) - Surif, Misni; Madon, Zainal; Abu Samah, Asnarulkhadi; Muhammad, Mahazan; Sulaiman, Abdul Hadi (2016)
Knowledge Transfer Program (KTP) which started in 2011 is one of the government's initiatives through the Economic Planning Unit (EPU) and the Ministry of Higher Education (MoHE) to promote the involvement of the Public University in collaboration with the community and local industry. The main goal of the KTP program is to improve the communities’ livelihood and increase of industry revenue. The question is how far the effectiveness of this KTP achieves the set objectives. Thus, a study was conducted to evaluate the impact and effectiveness of KTP in the communities involved. This paper aims to share experiences, obstacles and challenges of implementing the evaluation process and present an appropriate generic measurement parameter to evaluate some type of the KTP community category projects. A total of 16 KTP communities’ category projects for the first rolling (2011 – 2013) involved in these impact studies. Based on the obstacles and challenges encountered during the ongoing the research process, some suggestions are put forward to improve the KTP communities’ category project evaluation in the future.